Pengaruh Gaya Kepemimpinan dan Pelatihan Terhadap Kinerja Karyawan Perumdam Tirta Tarum Karawang - Yusuf Rofi Al-Qodiri; Danny Ramdani (Jurnal Ilmiah Wahana Pendidikan, 2022)
This research was conducted to find out how much influence leadership and training styles have on the performance of Perumdam Tirta Tarum Karawang employees. This research method uses quantitative methods with descriptive verifiability. The data collection technique used in this study was respondent data that researchers collected as many as 175 respondents and previous studies. This study uses path analysis to find out how much influence leadership and training styles have on employee performance. The signification value of leadership style was (0.000) < (0.05) and training (0.012) < (0.05), the leadership style and training variables had a significant positive influence on employee performance with a total influence of 39.9% and 60.1% influenced by other variables that were not studied. Keywords: Leadership Style, Training, Performance, Employees.